SIGNIFIKANSI AKSI MELELA DALAM MANGA SHIMANAMI TASAGORE (2015) - Firdausy, Erina; Anggraeni, Dewi (Paradigma: Jurnal Kajian Budaya, 2023)
This study examines the concept of coming out as part of queer narrative within Shimanami Tasogare (2015), a manga by Kamatani Yūki. Although coming out has become an important concept within LGBTQ, previous related research tends to see coming out as a one-time achievement. This study analyses the significance of coming out in Shimanami Tasogare by using the queer narrative approach. This study applies Klein et al.’s theory (2015) which argues that coming out is a dynamic and non-linear social process. This study uses text analysis and compositional interpretation (Rose, 2001) as research method. Results show that coming out plays a significant role for the characters who have done it for two reasons. First, coming out is a way for LGBTQ individuals to remove the compulsion to hide their non-heteronormative identity. Second, coming out is also a way to educate people who misunderstand or have misconceptions about LGBTQ. This study found that Shimanami Tasogare has succeeded in depicting the complexity of LGBTQ identity without trapping itself within the traditional queer narrative which assumes that coming out is a linear process.